After 2015: International Development Policy at a Crossroads - Sumner, A. author. aut Link
XII, 215 p. 2 illus.
Keywords: The Millennium Development Goals (MDGs) have played a major role in focusing policy since their original incarnation in the mid to late 1990s but what happens when we no longer have the MDGs - what will guide policy after 2015? This book discusses the world and development policy up to and beyond 2015.